Hubungan Antara Vertigo Dengan Riwayat Jatuh Pada Lanjut Usia Di Kota Surakarta - FAUZIAH, Enny, Yulisna Mutia Sari, SSt.FT., M.Sc (), Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2015)
Background: Vertigo is not a disease but a symptom of a disease. Vertigo causes by the disturbance in the Vestibular system. In the elderly people's case, the decrease of the vestibular system can cause balance disturbance. It happens because the changes of the progressive fragmentation of statoconia utricle and saccule which cause the reduction of elderly people's response toward the gravity acceleration and make them fall. The symptoms of vertigo can be measured by vertigo symptom scale- short form (VSS- FS) in which if the total score is e"=20 it can be said that it is vertigo positive. Research purposes: to know the relation between vertigo and the fall history of the elderly people in Surakarta Research benefit: to be able to know the relation between vertigo and the fall history of the elderly people in Surakarta. Research method: this research is an observational research with cross sectional approach. The sampling technique used is simple random sampling with 71 samples to find out the relation between vertigo and the fall history of the elderly people. The measurement of vertigo uses Vertigo Symptom Scale- short form (VSS-SF) by summing up the score in every number whereas the measurement of the fall history uses Wilhan research questionnaire, 2009 by identifying the fall history. The correlation test uses Chi Square test with 95% degree of confident. Research findings: Based on Chi-Square test, it is known that p-value score is 0,001 < 0,005 so H0 is declined and Hα is accepted. It can be interpreted that there is a relation between vertigo and the fall history of the elderly people in Surakarta Conclusion: There is a relation between vertigo and the fall history of the elderly people in Surakarta.